Pengembangan Aplikasi Monitoring Informasi Proyek Berbasis Web Menggunakan Metode ICONIX Process (Studi Kasus: PT Telkom Akses Witel Semarang) - Emmanuel Bagas Agustha; Satriyo Adhy; Dinar Mutiara Kusumo Nugraheni (Jurnal Masyarakat Informatika, 2024)
This research explores the importance of a project information monitoring application in supporting effective decision-making within companies, with a focus on PT Telkom Akses Witel Semarang. Currently, internal reports are manually compiled, leading to data integration imperfections, difficulties in monitoring job billing, and potential errors in decision-making. These issues were identified as key factors motivating the development of a web-based "Project Information Monitoring" application. The application is designed to address these problems by improving operational ease, accurately monitoring job billing, and centralizing divisional reports. This research employs the ICONIX Process methodology, which plays a crucial role in ensuring that the application’s design and development are structured and well-documented. The application is developed using the Laravel 10 framework with a Model View Controller (MVC) approach, ensuring an efficient and correct development process. The application was tested using black box testing with various scenarios based on predefined use cases. The test results demonstrate that the application meets user needs, as evidenced by acceptance in each test scenario.